Seed production of hybrid maize: IITA research guide, No. 59 - Kim, S.K.; Kling, J.; Weber, G. (1999)
Hybrid maize seed was the first commercially available F1 seed. Inbred lines serve as parents for commercial production of single-cross hybrid seed. Cooperation between seed companies, research institutes, and government institutions is essential to the successful development of productive hybrids. Commercial hybrid seed production requires proper ecological location, agronomic practices, pest and disease control. Additional elements necessary for a successful hybrid seed industry include seed handling, treatment, and packaging equipment and materials, appropriate seed storage environment, and an efficient seed distribution and marketing infrastructure. Seed production in the savanna is often better than in the forest area of sub-Saharan Africa. The role of governmental seed certification agencies is to test seed viability and purity and to issue certificates to seed companies for seed marketing.